Functional Understanding of Quantum Technologies is Essential to the Ethical Debate About Their Impact. - de Jong, Eline (NanoEthics, 2026)
As the innovative potential of quantum technologies comes into focus, so too does the urgent need to address their ethical implications. While many voices highlight the importance of ethical engagement, less attention has been paid to the conditions that make such engagement possible. In this article, I argue that one key condition is technological understanding: the cognitive skill to recognise how a technology can be used to realise an aim. More specifically, I claim that meaningful ethical discussion depends, first and foremost, on understanding a technology’s functional capabilities: what it can do and what it can be used for. Presenting such ‘functional understanding’ as an epistemic requirement helps guide efforts to improve understanding of quantum technologies in support of ethical engagement. Such efforts often focus on explaining, in broad strokes, the underlying physics and technical details. While technical insights may indeed support ethical analysis, they are neither sufficient nor always necessary for grasping the broader societal and ethical implications of a technology. What is indispensable for such discussions is an understanding of its (potential) functions. To foster ethical engagement with quantum technologies, I therefore advocate a functions-oriented approach to promoting understanding of these technologies. At first glance, presenting technological understanding as an epistemic requirement for meaningful ethical engagement may seem to raise the bar for participation. However, by decoupling functional understanding from technical expertise, this condition becomes attainable for a broader group, contributing not only to a well-informed but also to a more inclusive ethical debate.